The Poetic Necessity in the Book Al-Muwashah by Al-Marzobani (384AH): A Grammatical Study (Journal of the College of Education for Women, 2024)
This study aims to understand the grammatical effort of Abu Obaid Allah AL-Marzobani in his reference to grammatical issues in his book "AL-muwashah” through the complete extrapolation of the book and the extraction of all grammatical issues, and then discuss and balance it with the considered sources and the opinions of linguists who lived with AL-Marzobani or preceded him, and shows the grammarian school to which the owner of the muwashah tends. The study also aims to show the role played by poetic necessity in directing grammatical judgments. These methodological steps helped the research achieve its objectives and answer its questions. This study is important in that it deals with grammatical analysis of a topic that has not been touched before; it opens the door for further studies and research on the grammatical efforts of AL-Marzobani. The research concludes that the efforts of the grammatical views of Al-Marzobani and the views he adopted were not intended for themselves, but were presented to him while dealing with a set of poetic and critical issues, so he addressed them with his grammatical knowledge, and therefore we see the grammatical opinions that he conveyed are clear directly, and lack in large part of them evidence or opinions. The study also concluded that thirteen grammatical issues were directed as poetic necessity, out of twenty-three issues that are the sum of the grammatical issues mentioned in the muwashah.